9x + 8 = 50 - 2x
Simplifying
9x + 8 = 50 + -2x
Reorder the terms:
8 + 9x = 50 + -2x
Solving
8 + 9x = 50 + -2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '2x' to each side of the equation.
8 + 9x + 2x = 50 + -2x + 2x
Combine like terms: 9x + 2x = 11x
8 + 11x = 50 + -2x + 2x
Combine like terms: -2x + 2x = 0
8 + 11x = 50 + 0
8 + 11x = 50
Add '-8' to each side of the equation.
8 + -8 + 11x = 50 + -8
Combine like terms: 8 + -8 = 0
0 + 11x = 50 + -8
11x = 50 + -8
Combine like terms: 50 + -8 = 42
11x = 42
Divide each side by '11'.
x = 3.818181818
Simplifying
x = 3.818181818